Value of pretreatment serum lactate dehydrogenase as a prognostic and predictive factor for small‐cell lung cancer patients treated with first‐line platinum‐containing chemotherapy. Issue 23 (1st November 2021) - He, Man; Chi, Xiaorui; Shi, Xinyan; Sun, Yang; Yang, Xue; Wang, Leirong; Wang, Bingrui; Li, Hongmei
Abstract : Background: The current study aimed to evaluate the serum pretreatment lactate dehydrogenase (LDH) and overall survival (OS) in small cell lung cancer (SCLC) patients who received first‐line platinum‐containing chemotherapy. Methods: A total of 234 SCLC patients, who received first‐line platinum‐based chemotherapy between 2013 and 2018, were retrospectively analyzed. The data of hematological characteristics, age, gender, ECOG score, staging, metastatic site, smoking history, chemotherapy cycle, thoracic radiotherapy and hyponatremia were collected. Overall survival was calculated using the Kaplan‐Meier method. The statistically significant factors in the univariate analysis were selected for the multivariate COX model analysis. Results: Age, ECOG score, stage, thoracic radiotherapy, hyponatremia, liver metastasis, brain metastasis, bone metastasis, LDH, NSE and neutrophil‐to‐lymphocyte ratio (NLR) were closely correlated to OS in the univariate analysis. Furthermore, the multivariate analysis revealed that age (<65 years), ECOG score (<2 points), limited‐stage (LD), thoracic radiotherapy and LDH <215.70 U/L were the independent prognostic factors for survival. The median OS time was worse for patients with LDH ≥215.70 U/L. In the subgroup analysis, LDH ≥215.70 U/L was significant for survival in both limited and extensive disease. Patients who achieved CR + PR in the first‐line treatment had lower initial LDH levels. It was found that the pretreatment LDH increased the incidence of patients with liver metastasis. Conclusions: Positive independent prognostic factors for SCLC patients were age < 65 years old, ECOG score < 2 points, LD‐SCLC, and pretreatment LDH <215.70 U/L. These factors may be useful for stratifying patients with SCLC for treatment approaches. Key points: Significant findings of the study: Age < 65 years old, ECOG score < 2 points, LD‐SCLC, and pretreatment LDH <215.70 U/L are the positive independent prognostic factors for SCLC patients. What this study adds: The current study provided more references for SCLC diagnosis and treatment and determined more factors for stratifying patients with SCLC for treatment approaches. Abstract : The current study aimed to evaluate the serum pretreatment lactate dehydrogenase (LDH) and overall survival (OS) in small‐cell lung cancer (SCLC) patients who received first‐line platinum‐containing chemotherapy. A total of 234 SCLC patients, who received first‐line platinum‐based chemotherapy between 2013 and 2018, were retrospectively analyzed. Age <65 years old, ECOG score <2 points, LD‐SCLC, and pretreatment LDH <215.70 U/L are the positive independent prognostic factors for SCLC patients.